Stability indicating HPLC and spectrophotometric methods for the determination of bupropion hydrochloride in the presence of its alkaline degradates and related impurity - Samah S. Abbas; Mohamed R. Elghobashy; Rafeek F. Shokry; Lories I. Bebawy (Faculty of Pharmacy, Cairo University, 2012)
Four sensitive and selective stability-indicating methods for the determination of bupropion hydrochloride in the presence of its alkaline degradates, related impurity, 3-chlorobenzoic acid, and in its pharmaceutical formulation were developed. Method A is an isocratic reversed phase HPLC, good separation between bupropion hydrochloride, its alkaline degradates and related impurity was achieved using a mobile phase of 1.2% w/v ammonium dihydrogen phosphate pH 4.5 and acetonitrile (80:20, v/v) and detection at 210 nm. Method B is based on the first derivative (D1) measurement of the drug at 259 nm, zero contribution point of its alkaline degradates and related impurity. Method C is based on the resolution of the drug, its alkaline degradates and related impurity by first derivative ratio spectra (DD1). Method D is based on the determination of bupropion hydrochloride and its impurity by the Q value method at 248 nm, 227 nm and at isoabsorptive point 237 nm. These methods are successfully applied for the determination of bupropion hydrochloride in bulk powder, pharmaceutical formulation and in the presence of its alkaline degradates and related impurity. The results obtained are statistically analyzed and there are no significant differences between the four methods and the official one with respect to accuracy and precision.